2016
DOI: 10.1016/j.anorl.2016.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Salivary gland-sparing helical tomotherapy for head and neck cancer: Preserved salivary function on quantitative salivary gland scintigraphy after tomotherapy

Abstract: Helical tomotherapy reduced the incidence and severity of xerostomia. A mean dose to the parotid between 20 and 26Gy allowed preservation of salivary function without compromising treatment efficacy. However, parotid-sparing HT requiring a mean dose less than 20Gy is associated with an increased risk of recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
0
9
0
1
Order By: Relevance
“…The QUANTEC consortium (6,28) identified a mean parotid gland dose of 26 Gy as a critical threshold for the preservation of salivary function. However, in IMRT clinical practice, it is often challenging to comply with this recommendation, since a detrimental impact on target coverage can't be completely minimized (29). Furthermore, it has been demonstrated that a late recovery of salivary function is feasible, even in cases of overt xerostomia shortly after RT (30).…”
Section: Head and Neck Radiotherapy: Parotid Glandsmentioning
confidence: 99%
“…The QUANTEC consortium (6,28) identified a mean parotid gland dose of 26 Gy as a critical threshold for the preservation of salivary function. However, in IMRT clinical practice, it is often challenging to comply with this recommendation, since a detrimental impact on target coverage can't be completely minimized (29). Furthermore, it has been demonstrated that a late recovery of salivary function is feasible, even in cases of overt xerostomia shortly after RT (30).…”
Section: Head and Neck Radiotherapy: Parotid Glandsmentioning
confidence: 99%
“…Previous studies have demonstrated that the severity of xerostomia were associated with the hypo-function of the salivary glands due radiation damage, which was found to be dependent on the amount of radiation dose delivered to the glands (16, 17). Because of this, submandibular gland (SMG)-sparing and parotid gland (PG)-sparing techniques have been suggested to minimize the damage of salivary glands in recent studies (18). Several studies including Wang and Eisbruch (19) and Voordeckers et al (20) supported that the mean parotid dose should be kept below 26 Gy for the preservation of salivary gland function.…”
Section: Radiation Induced Damage To Salivary Glandsmentioning
confidence: 99%
“…Z. B. konnte so gezeigt werden, dass die Anwendung der helikalen Tomotherapie, eine besondere Form der intensitätsmodulierten Strahlentherapie (IMRT), bei Kopf-Hals-Tumoren eine präzisere Bestrahlung und somit auch effektivere Schonung der Speicheldrüsen ohne Reduktion der therapeutischen Effektivität ermöglicht [18]. Gegenstand der aktuellen Forschung ist zudem die Xerostomie als Folge einer auf das prostataspezifische Membran-Antigen (PSMA) ausgerichteten Radionuklidtherapie.…”
Section: Indikationen Und Klinische Relevanzunclassified